Two-Step Progressive Transcrestal Sinus Augmentation Using a 4.5 mm Unloaded Implant as a “Temporary Implant” in Highly Atrophic Ridge: Case Report - Anitua, Eduardo (European Journal of Dentistry, 2023)
Severe atrophic posterior maxillary ridge (residual bone height < 3 mm) could be a challenging situation to place dental implants. Several treatment options have been proposed, but some of them may require advanced surgical skills to achieve best results. In this article, we present a novel and easier technique to allow implant placing in localized areas of severe atrophy. In a first step, a 4.5-length extra-short (unloaded) implant is placed after a transcrestal maxillary sinus floor augmentation (MSFA). After the gained apical bone consolidation, this “temporary implant” is atraumatically removed and a longer and wider definitive implant is placed to support the definitive single restoration. The case of a 45-year-old female treated with this approach is also presented. The patient suffered a severe resorption in the upper right molar area after a tooth extraction. Four months after the “temporary implant” placement and MSFA grafting with plasma rich in growth factors and autologous bone, 3 mm of dense apical bone gain could be observed. In a second surgical time, the 4.5 mm-length “temporary implant” was removed, and a 5.5 mm-length “definitive implant” was placed. This second implant was placed in a denser type 1 (1,000 Hounsfield Unit) new formed apical bone. Four months later, the implant was loaded with a screw-retained crown over a transepithelial (intermediate abutment). After 1-year follow-up, the implant was in health and no mechanical or biological complications were noticed. The satisfactory results of this case encourage the realization of new studies to elucidate its reproducibility.
Keywords: sinus floor augmentation; short implants; bone atrophy